PENGARUH KUALITAS PELAYANAN, HARGA DAN LOKASI TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pada Milala Service Station Medan) - Barus, Yessi Yospita; Sinaga, Ria Veronica; Sagala, Roslinda (UNIKA Santo Thomas, 2020)
This study aims to determine whether there is an influence between service quality, price and location on customer satisfaction either partially or simultaneously on Milala Service Station Medan. The population of this research is the service users of Milala Service Station during the study period with a total sample of 82 respondents with purposive sampling technique. Data collection method with a questionnaire. Data analysis technique used is multiple linear regression. The multiple linear regression equation obtained from the test results is Y = -0,636 + 0,145X1 + 0,224X2 + 0,236X3 + ei, meaning that simultaneous service quality, price and location have a positive and significant effect on customer satisfaction of users of MilalaService Station Medan services. However, location variable is the most influential variable on customer satisfaction of service users of Medan Milala Service Station. With a regression coefficient of 0.236 or 23.6%, this means that Milala Medan Service Station should maintain its existing location. R square of 0.401, meaning that variations in customer satisfaction can be explained by variations in service quality, price and location by 40.1% and the remaining 59.9% can be explained by other variables not explained in this study. From the results of research and discussion, Medan Milala Service Station should further develop and maintain indicators of service quality, price and location available at Medan Milala Service Station, so that employees can further enhance customer satisfaction.